Fabrication and characterization of self supporting 48Ti thin films. (July 2022) - Arora, H.; S.R., Abhilash; Umapathy, G.R.; Kapil, Ashutosh; Behera, B.R.
Abstract: Fabrication of self-supporting 48 Ti films of thickness ≈ 500 μ g /cm 2 using 100 mg of the material by electron-beam evaporation technique in a high vacuum environment has been discussed. A simple and novel method of slowly evaporating the enriched material has been adopted in contrast to complex setup modifications utilized in earlier studies. Various techniques employed for successful fabrication of thin films have been discussed. The thickness measurements and characterizations of fabricated thin films have been carried out using advanced techniques viz., α -transmission method, Rutherford Backscattering Spectrometry (RBS), Energy Dispersive X-ray Spectrometry (EDS), Field Emission Scanning Electron Microscopy (FE-SEM), and Energy Dispersive X-ray Fluorescence (EDXRF). One of the fabricated targets has successfully been used in nuclear physics experiments. Highlights: A novel method of slowly evaporating 48 Ti target followed by annealing has been discussed for the fabrication of thin films. e-beam evaporation in high vacuum environment has been followed. Characterization techniques such as α -transmission method, RBS, EDS, FE-SEM and EDXRF have been used for target characterization. Targets in the thickness range (319–548) μ g / cm 2 have been fabricated. Calcium Iodide has been used as a parting agent.